Nanoparticle-Based Approaches towards the Treatment of Atherosclerosis - Artur Y. Prilepskii; Nikita S. Serov; Daniil V. Kladko; Vladimir V. Vinogradov (MDPI AG, 2020)
Atherosclerosis, being an inflammation-associated disease, represents a considerable healthcare problem. Its origin remains poorly understood, and at the same time, it is associated with extensive morbidity and mortality worldwide due to myocardial infarctions and strokes. Unfortunately, drugs are unable to effectively prevent plaque formation. Systemic administration of pharmaceuticals for the inhibition of plaque destabilization bears the risk of adverse effects. At present, nanoscience and, in particular, nanomedicine has made significant progress in both imaging and treatment of atherosclerosis. In this review, we focus on recent advances in this area, discussing subjects such as nanocarriers-based drug targeting principles, approaches towards the treatment of atherosclerosis, utilization of theranostic agents, and future prospects of nanoformulated therapeutics against atherosclerosis and inflammatory diseases. The focus is placed on articles published since 2015 with additional attention to research completed in 2019-2020.